ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PENGOLAHAN KOPRA DI KOTA RAHA - La Idin, La Idin (JURNAL EKONOMI UHO, 2016)
This study aims to find out the determinant of labor productivity of copra industry in Kusambi and Napano Kusambi District Raha City. This research analyzed through descriptive analysis. Sampel of this research is 12 labor, 8 labor of Kusambi District from 4 unit factory and 4 labor of Napano Kusambi District from 2 unit factory. The finding showed that labor productivity of Kusambi District higer than labor productivity of Napano Kusambi District. Determinant of labor productivity of copra industry in Raha City is training of labor. Labor participation proportion in training of copra production for Kusambi District is 62,5 percent; and for Napano Kusambi District is 50 percent.